2022
DOI: 10.1111/acem.14443
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital airway management for out‐of‐hospital cardiac arrest: A nationwide multicenter study from the KoCARC registry

Abstract: Aim This study investigated whether prehospital advanced airway management (AAM) is associated with improved survival of out‐of‐hospital cardiac arrest (OHCA) compared with conventional bag–valve–mask (BVM) ventilation. Methods We investigated the neurologically favorable survival of adult patients with OHCA who underwent BVM or AAM using the Korean Cardiac Arrest Research Consortium (KoCARC), a multicenter OHCA registry of Korea. The differences in clinical characteristics were adjusted by matching or weighti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
(53 reference statements)
0
5
0
Order By: Relevance
“…Finally, regarding prehospital advanced airway management (AAM) in patients with OHCA[ 20 , 21 ], some studies have shown that endotracheal intubation (ETI) can improve the probability of sustained ROSC, survival to hospital discharge, and neurologic outcomes[ 22 ]. In the present study, ETI was significantly associated with P-ROSC (OR: 8.28, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, regarding prehospital advanced airway management (AAM) in patients with OHCA[ 20 , 21 ], some studies have shown that endotracheal intubation (ETI) can improve the probability of sustained ROSC, survival to hospital discharge, and neurologic outcomes[ 22 ]. In the present study, ETI was significantly associated with P-ROSC (OR: 8.28, P < 0.001).…”
Section: Discussionmentioning
confidence: 99%
“…In a study using national data in the Republic of Korea, the prehospital AAM was 65.0%. Our city’s rate was higher than that of other countries and the domestic average [ 21 ]. However, it is not clear whether better prehospital AAM leads to better outcomes in OHCA.…”
Section: Discussionmentioning
confidence: 98%
“…This may be due to the fact that complicated interventions 23 are usually performed to take care of these patients during the transport; hence, physicians could not have enough time to perform POCUS. However, previous studies [24][25][26] demonstrated the feasibility and the utility of POCUS in out-of-hospital cardiac arrest patients, which showed the advantage of POCUS used.…”
Section: Discussionmentioning
confidence: 99%